Coordination of Respiration, Swallowing, and Chewing in Healthy Young Adults - Hao, Naohito; Sasa, Anna; Kulvanich, Sirima; Nakajima, Yuta; Nagoya, Kouta; Magara, Jin; Tsujimura, Takanori; Inoue, Makoto (Frontiers in Physiology, 2021)
Examining the coordination of respiration and swallowing is important for elucidating the mechanisms underlying these functions and assessing how respiration is linked to swallowing impairment in dysphagic patients. In this study, we assessed the coordination of respiration and swallowing to clarify how voluntary swallowing is coordinated with respiration and how mastication modulates the coordination of respiration and swallowing in healthy humans. Twenty-one healthy volunteers participated in three experiments. The participants were asked to swallow 3 ml of water with or without a cue, to drink 100 ml of water using a cup without breathing between swallows, and to eat a 4-g portion of corned beef. The major coordination pattern of respiration and swallowing was expiration–swallow–expiration (EE type) while swallowing 3 ml of water either with or without a cue, swallowing 100 ml of water, and chewing. Although cueing did not affect swallowing movements, the expiratory time was lengthened with the cue. During 100-ml water swallowing, the respiratory cycle time and expiratory time immediately before swallowing were significantly shorter compared with during and after swallowing, whereas the inspiratory time did not differ throughout the recording period. During chewing, the respiratory cycle time was decreased in a time-dependent manner, probably because of metabolic demand. The coordination of the two functions is maintained not only in voluntary swallowing but also in involuntary swallowing during chewing. Understanding the mechanisms underlying respiration and swallowing is important for evaluating how coordination affects physiological swallowing in dysphagic patients.